Infrastructure factor of the eurasian integration - A., Makasheva K.; A, Konuspayev Ye.,; A, Bernov V. (Farabi Journal of Social Sciences, 2019)
Abstract. World political processes in the 21st century are in many respects formed under the influence of development of transport and logistics potential. The geographical position of the Eurasian Economic Union facilitates construction of transport and logistics routes of both regional and global significance. This is a key factor for mutual competitiveness and dynamic economic growth in a rapidly changing and complex world. That’s why article is devoted to the transport infrastructure development within the Eurasian space. The aim of the article is to provide complex analysis of the key factors affecting transport integration within the Eurasian space and identifying priorities for the Eurasian transportation potential development. The methodological base includes systems analysis, historical and comparative methods of research, institutional, structural and functional approaches. Results of research have theoretical and practical value for foreign policy and economic departments. Its conclusions can be used for predicting of tendencies in the sphere of development of the international transport corridors within the Eurasian space.